Analytical nominations in Ukrainian meteorological terminology (semantics structure) - Заверющенко, Микола Петрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article considers and analyses analytical nominations of Ukrainian meteorological terminology, investigates their semantic features and patterns of forming. Here are defined and described structural models of forming multi-component meteorological terms, established the degree of productivity of separate structural models.